PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI 32 LUBUKLINGGAU - Dinda Permata; Charli, Leo; Syaprizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low Indonesian language learning outcomes of Grade V students at SD Negeri 32 Lubuklinggau. The study aimed to determine whether the Indonesian language learning outcomes of Grade V students significantly met the Minimum Learning Mastery Criteria (KKTP) following the implementation of the Think-Pair-Share (TPS) learning model. A pre-experimental method with a one-group pretest-posttest design was employed. The population consisted of all Grade V classes at SD Negeri 32 Lubuklinggau, with Class VB comprising 19 students—serving as the sample. Data collection was conducted using tests. The results showed that the average pretest score was 46.44, which increased to 80.80 in the posttest. The t-test results indicated that t-count > t-table (4.7217 > 1.734) at a significance level of α = 0.05. Thus, it can be concluded that the application of the Think-Pair-Share (TPS) learning model resulted in students significantly meeting the KKTP.